152 Anxiety was expressed more in gynecologic cancer patients on treatment: a retrospective study from Japan under the statement of emergency for COVID-19 pandemic. (13th November 2020) - Mogami, T; Onuma, E; Kamiya, N; Kiyose, A; Sato, R; Saito, S; Aoki, M; Koga, E; Saito, S; Okada, Y; Sukegawa, A; Miyagi, E; et al.
Abstract : Introduction: Cancer patients frequently have problems related to anxiety or depression. Under the COVID-19 pandemic, people feel anxiety though each extent differs a lot. In outpatient clinics, not few cancer patients expressed their anxiety by asking, complaining, or just shedding tears. Since the virus seems to come back again in years, we evaluated the anxiety and depression in gynecologic cancer patients under the current first wave. Methods: A retrospective study was planned. Gynecologic cancer patients in our hospital who had tests for anxiety and depression during the Japanese government-ordered state of emergency against COVID-19 were included. We use self-filling tests of 'distress temperature scale' and 'Hospital Anxiety and Depression Scale (HADS)' to patients with cancer or after cancer. Results: 34 patients were included. 12 patients visited just for follow-up after treatment, and 22 were on treatments. Almost all patients were willing to do and easily completed the tests. Each score excluding depression score on HADS was higher in patients on cancer treatment than in follow-up after treatment. One third of on-treatment patients showed significant high anxiety score. Several patients who had tests three or more times expressed recovering trend by day passed. Conclusions: Self-filling tests of 'distress temperature scale' and HADS are useful. Especially on-treatment patients are vulnerable to the pandemic stress. We continue the careful evaluation and will work proactively against the future pandemic.